Ocean Acidification: An Introduction - Joshua T. Patterson; Lisa S. Krimsky (EDIS)
Ocean acidification (OA) generally refers to the ongoing decrease in ocean pH. Ocean acidification is caused primarily by the oceanic uptake of excess carbon dioxide (CO2) from the atmosphere. Other impacts related to climate change (increased sea level rise, coastal flooding and extreme weather events) often receive more attention than OA, but the acidification of the Earth’s oceans is well documented and is a major concern for the marine science community. This publication is the first in a series that addresses ocean acidification in Florida. It specifically explains the changes that are occurring to the chemistry of our coastal and oceanic waters because of elevated carbon dioxide levels. Additional publications address potential environmental, economic, and social implications for Florida.